Caudal Duplication Syndrome: the Vital Role of a Multidisciplinary Approach and Staged Correction - Samuk, Inbal; Levitt, Marc; Dlugy, Elena; Kravarusic, Dragan; Ben-Meir, David; Rajz, Gustavo; Konen, Osnat; Freud, Enrique (European Journal of Pediatric Surgery Reports, 2016)
Caudal duplication syndrome is a rare entity that describes the association between congenital anomalies involving caudal structures and may have a wide spectrum of clinical manifestations. A full-term male presented with combination of anomalies including anorectal malformation, duplication of the colon and lower urinary tract, split of the lower spine, and lipomyelomeningocele with tethering of the cord. We report this exceptional case of caudal duplication syndrome with special emphasis on surgical strategy and approach combining all disciplines involved. The purpose of this report is to present the pathology, assessment, and management strategy of this complex case.
Keywords: caudal duplication syndrome; anorectal malformation; rectal duplication; colonic duplication; genitourinary duplication